2023
DOI: 10.1002/ags3.12671
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of serum creatinine and cystatin C ratio as a screening tool for predicting prognosis in patients with pancreatic cancer

Abstract: AimThis study aimed to evaluate the usefulness of the serum creatinine/cystatin C (Cr/CysC) ratio as a prognostic factor after pancreatic surgery in patients with pancreatic cancer.MethodsWe retrospectively analyzed the data of 88 patients with pancreatic ductal carcinoma who underwent pancreatic surgery from January 2017 to December 2020. CysC measured from frozen serum samples and circulating Cr levels were used to calculate the Cr/CysC ratio. The cutoff value of the Cr/CysC ratio was determined using receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Previous studies have also shown that the Cr/CysC ratio is a surrogate marker for malignancy, along with sarcopenia being a poor prognostic factor for malignant disease. We have shown that Cr/CysC ratio is a useful surrogate marker in hepatocellular carcinoma and in pancreatic cancer patients undergoing surgery [12,13]. However, the usefulness of the Cr/CysC ratio in patients with biliary tract cancer has not been reported.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have also shown that the Cr/CysC ratio is a surrogate marker for malignancy, along with sarcopenia being a poor prognostic factor for malignant disease. We have shown that Cr/CysC ratio is a useful surrogate marker in hepatocellular carcinoma and in pancreatic cancer patients undergoing surgery [12,13]. However, the usefulness of the Cr/CysC ratio in patients with biliary tract cancer has not been reported.…”
Section: Introductionmentioning
confidence: 95%
“…Harimoto et al revealed that the Cr/CysC ratio had potential as a surrogate marker in patients with hepatocellular carcinoma undergoing hepatic resection[12]. Tsukagoshi et al also showed that the Cr/CysC ratio could be a useful screening tool for predicting prognosis in pancreatic cancer patients[13]. Many of these previous studies concluded that the Cr/CysC ratio could predict prognosis because of the relationship with decreased muscle mass (in other words, sarcopenia).…”
mentioning
confidence: 99%
“…Leveraging the characteristics of creatinine and Cystatin C, the creatinine-to-cystatin C ratio (CCR) was initially proposed by Kashani et al as a simplified method for diagnosing sarcopenia in patients (6). Since then, CCR has been extensively studied and established as a biomarker for the prognosis in patients with critically illness (7,8), hypertension (9), type 2 diabetes (10, 11) and cancer (12)(13)(14)(15)(16)(17). Recently, a retrospective study reported that low CCR was an independent biomarker of poor prognosis in nonsmall cell lung cancer (NSCLC) patients treated with PD-1 monotherapy (18).…”
Section: Introductionmentioning
confidence: 99%